Elimination of the antibiotic doxycycline using a helicoidal flux photoreactor: By-products and eco-toxicity assessment (2023)
INTRODUCTION DOX molecular structure Doxycycline (DOX) is an antibiotic belonging to the tetracycline family used in the treatment of infectious diseases caused by different types of bacteria and protozoa, it is the case of pneumonia, chlamydia, and cholera. Additionally, due to their incomple temetabolization, antibiotics are excreted without modifications into the sewage system via urine or feces, which together with the fact that most of the wastewater treatment plants (WWTPs) do not have an appropriate design toremove them completely, they are discharged directly into water sources, which represents a potential risk for ecosystems, and even for humans, due to the proliferation of bacterial resistance. DOX has been detected in water bodiesin some Latin-American countries like Brazil and Colombia.